Interferência do parecoxibe sobre a função renal e lesão de rins submetidos ao estresse isquêmico: trabalho experimental em ratos com uso de NGAL como marcador da função renal - Calistro Neto, José Pedro [UNESP] (2014)
Background and aims: nonsteroidal anti-inflammatory drugs (NSAIDs) have been proved to be effective, in a multidimensional approach, at reducing the opioid consumption during the postoperative acute pain. Although the NSAIDs may affect the renal function, there are few published data related to the use of coxibs and the kidney function. The early biomarkers of acute renal injury (EBARI) may be important tool to determining the actual risk associated with the use of coxibs NSAIDs in the perioperative period. Methods: after approval by Experimental Ethics Committee, 40 male Wistar rats were randomly assigned into four groups. Under general anesthesia, and depending on the assigned group, rats underwent renal ischemia and reperfusion. Parecoxib was injected in two of the groups to evaluate the coxib intluence on the renal function. Parametric data, serum neutrophil gelatinase-associated lipocalin (NGAL), an EBARI, and right and left renal histology were used to evaluate there renal function. Results: the animals of ischemia group which did not receive parecoxib showed the highest NGAL serum level, as well as the most severe tubular injury. The animals on ischemia group which received parecoxib showed NGAL plasmatic levels and tubular injury similar to the groups not subjected to renal ischemia. Conclusion: on this experimental model, parecoxib showed protective renal properties